Anti-Trimeresurus albolabris venom IgY antibodies: preparation, purification and neutralization efficacy. Issue 1 (December 2016) - Duan, Hai-long; He, Qi-yi; Zhou, Bin; Wang, Wen-wen; Li, Bo; Zhang, Ying-zheng; Deng, Qiu-ping; Zhang, Ying-feng; Yu, Xiao-dong
Abstract Background Snakebite incidence in southwestern China is mainly attributed to one of the several venomous snakes found in the country, the white-lipped green pit viperTrimeresurus albolabris . Since antivenom produced from horses may cause numerous clinical side effects, the present study was conducted aiming to develop an alternative antivenom antibody (immunoglobulin Y - IgY) from leghorn chickens. Methods IgY in egg yolk from white leghorn chicken previously injected withT. albolabris venom was extracted by water, precipitated by ammonium sulfate and purified by affinity chromatographic system. IgY was identified by SDS-PAGE, ELISA and Western blot, and its neutralizing assay was conducted on mice. Results Chickens injected multiple times withT. albolabris venom elicited strong antibody responses, and from their egg yolk IgY was isolated and purified, which exhibited a single protein band on SDS-PAGE and two bands (about 65 and 35 kDa, respectively) under reduced conditions. Immunoblot analysis revealed that these IgY are polyclonal antibodies since they bind with most venom components. In the neutralizing assay, all mice survived while the ratios of IgY/venom reached up to 3.79 (50.0 mg/13.2 mg). Conclusions IgY antibody response was successfully conducted in white leghorn chicken injected withT. albolabris venom. IgY againstT. albolabris venom was obtained for the first time, and it exhibited strong neutralizing potency on mice. These results may lay a foundation for the development of IgY antivenom with clinical applications in the future.